Clinicopathological and genomic comparisons between different histologic components in combined small cell lung cancer and non-small cell lung cancer. (November 2018) - Lin, Mong-Wei; Su, Kang-Yi; Su, Te-Jen; Chang, Chia-Ching; Lin, Jing-Wei; Lee, Yi-Hsuan; Yu, Sung-Liang; Chen, Jin-Shing; Hsieh, Min-Shu
Highlights: Adenocarcinoma can transform into SCLC as a mechanism of resistance to TKIs. We investigated genetic profiles of combined SCLC/NSCLC patients. SCLC and NSCLC components showed a high consistency in EGFR/TP53/RB1 mutations. TP53 / RB1 inactivation may be an early event in the tumorigenesis of combined SCLC/NSCLC. The SCLC component may arise from NSCLC via activation of the ASCL1 pathway and PI3K/AKT1 signaling pathway. Abstract: Objective: Histologic transformation from adenocarcinoma to small cell lung cancer (SCLC) is one of the mechanisms of acquired resistance after epidermal growth factor receptor (EGFR) tyrosine kinase inhibitor (TKI) treatment. Furthermore, de novo combined SCLC/non-small cell lung cancer (NSCLC) have occasionally been reported; however, their mutational statuses and clinicopathological features have not yet been elucidated. In this study, we aimed to profile the genetic backgrounds of these 2 different histologic components by investigating patients with de novo combined SCLC/NSCLC as well as those with lung adenocarcinoma who experienced SCLC transformation after TKI treatment. Materials and methods: Four patients with de novo combined SCLC/NSCLC were investigated, as were 4 other patients with lung adenocarcinoma who experienced SCLC transformation after TKI treatment. The different histologic components of the tumors in each patient were tested for thyroid transcription factor-1, p40, synaptophysin, chromogranin A, p53, retinoblastoma protein (Rb), and achaete-scute homolog 1 (ASCL1) via immunohistochemistry, and were macroscopically dissected for mutational analysis using next-generation sequencing with the Oncomine Focus Assay and Comprehensive Assay panel. Results: The distinct histologic components in patients with de novo combined SCLC/NSCLC and those with adenocarcinoma exhibiting small cell transformation showed high consistency in EGFR/TP53/RB1 mutations, and expression patterns of p53 and Rb. A high frequency of activating mutations involving PI3K/AKT1 signaling pathway was observed in SCLC. Nuclear ASCL1 expression was present in SCLC but absent or barely present in adenocarcinoma in 7 cases. Conclusions: Our data imply that inactivation of TP53 / RB1 function is a possible early event in the histogenesis of synchronous and metachronous SCLC/NSCLC. Moreover, the non-adenocarcinoma (SCLC) component might arise from the adenocarcinoma (NSCLC) component through a mechanism that involves the activation of the ASCL1 and PI3K/AKT1 signaling pathways.